Integrated Nitrogen Management Influences the Yield Performance of Rice under Different Methods of Cultivation - Jat, A. L.; Srivastava, V. K.; Chongtham, S. K.; Singh, Rajesh Kumar (International Journal of Bio-resource and Stress Management, 2020)
The field studies were conducted during 2012 and 2013 at Banaras Hindu University, Varanasi, Uttar Pradesh, India. The experiments were undertaken on two rice hybrids cultivated under two different establishment techniques with integrated nitrogen management to evaluate the growth dynamics, production potential and nutrient removal of rice. Results revealed that the system of rice intensification (SRI) and rice cv. Arize-6444 recorded significantly higher growth attributes viz., number of tillers/hill, dry matter accumulation, crop growth rate and relative growth rate with almost yield attributes and yield with nutrient harvest index and total water productivity. The corresponding increment in grain and straw yield of rice under SRI to the tune of 14.66% and 13.12% over normal transplanting and rice hybrid Arize 6444 produced 8.63% and 5.32% higher grain and straw yield over PHB 71, respectively. Among the integrated nitrogen management practices, the application of 50% RDN+50% N through FYM+Azospirillum recorded significantly higher growth attributes, grain yield (6942 kg ha-1), protein content (7.80%), nutrient content, protein yield (542 kg ha-1) total nutrient uptake, total water productivity (5.90 kg/ha-mm) and nutrient harvest index of rice. The study concluded that the conjunctive application of inorganic fertilizer and organic manure with biofertilizer to rice hybrid ‘Arize-6444’ cultivation under SRI method for realizing higher yield of rice in eastern Uttar Pradesh.